Assessment of the Effectiveness of the Use of Services Provided by Management Companies of the Housing Fund - Rakhmatilla, Kholmurodov (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This scientific article shows the existing problems in the management of the housing stock in our country and ways to eliminate them, the peculiarities of today's management. The status of the services provided by the Housing Trust Companies, ways to increase the number of services and the circumstances of their assessment have been identified.